Hubungan Efikasi Diri dengan Pengambilan Keputusan Karir Siswa SMK (Universitas Muhammadiyah Metro, 2023)
The primary objective of this research is to assess and elucidate the extent of the connection between self-efficacy and career decision-making among students at SMK Negeri 54 Jakarta. This study adopts a quantitative approach with a correlational methodology. Data was collected by administering questionnaires designed to capture information related to both variables. The study population consisted of students in the twelfth grade at SMK Negeri 54 Jakarta, comprising 262 students. The sample size, determined using the Slovin formula and a simple random sampling technique, amounted to 159 students. The research employed the Pearson product-moment correlation analysis with the assistance of SPSS version 22 to analyse the data. The analysis results revealed a correlation coefficient of 0.647, indicating a significant and positive correlation between self-efficacy and career decision-making in this study. This research contributes valuable insights into the relationship between self-efficacy and career decision-making among SMK Negeri 54 Jakarta students, shedding light on the importance of self-efficacy beliefs in shaping career choices.